Childhood Trauma, the HPA Axis and Psychiatric Illnesses: A Targeted Literature Synthesis - Murphy, Felim; Nasa, Anurag; Cullinane, Dearbhla; Raajakesary, Kesidha; Gazzaz, Areej; Sooknarine, Vitallia; Haines, Madeline; Roman, Elena; Kelly, Linda; O'Neill, Aisling; Cannon, Mary; Roddy, Darren William (Frontiers in Psychiatry, 2022)
Studies of early life stress (ELS) demonstrate the long-lasting effects of acute and chronic stress on developmental trajectories. Such experiences can become biologically consolidated, creating individual vulnerability to psychological and psychiatric issues later in life. The hippocampus, amygdala, and the medial prefrontal cortex are all important limbic structures involved in the processes that undermine mental health. Hyperarousal of the sympathetic nervous system with sustained allostatic load along the Hypothalamic Pituitary Adrenal (HPA) axis and its connections has been theorized as the basis for adult psychopathology following early childhood trauma. In this review we synthesize current understandings and hypotheses concerning the neurobiological link between childhood trauma, the HPA axis, and adult psychiatric illness. We examine the mechanisms at play in the brain of the developing child and discuss how adverse environmental stimuli may become biologically incorporated into the structure and function of the adult brain via a discussion of the neurosequential model of development, sensitive periods and plasticity. The HPA connections and brain areas implicated in ELS and psychopathology are also explored. In a targeted review of HPA activation in mood and psychotic disorders, cortisol is generally elevated across mood and psychotic disorders. However, in bipolar disorder and psychosis patients with previous early life stress, blunted cortisol responses are found to awakening, psychological stressors and physiological manipulation compared to patients without previous early life stress. These attenuated responses occur in bipolar and psychosis patients on a background of increased cortisol turnover. Although cortisol measures are generally raised in depression, the evidence for a different HPA activation profile in those with early life stress is inconclusive. Further research is needed to explore the stress responses commonalities between bipolar disorder and psychosis in those patients with early life stress